A STUDY ON CUSTOMER SATISFACTION TOWARDS THE DIGITAL BANKING FEATURES OFFERED BY PRIVATE SECTOR BANKS - Sayyad , Aiyesha; Subramanian , Pradeepa (Proceeding of International Conference on Social Science and Humanity, 2024)
General Background: The banking industry is crucial for economic development, serving as a catalyst for growth in both agricultural and industrial sectors. As banks support modernization through financial products, they significantly impact the livelihoods of farmers and the expansion of businesses, ultimately fostering economic prosperity. Specific Background: In an increasingly competitive landscape, exemplary customer service emerges as a vital component for banks to establish trust and loyalty. Effective communication, salesmanship, and courtesy are essential attributes for bank staff, directly influencing customer satisfaction and retention. Knowledge Gap: Despite the growing importance of digital banking features, there is limited research investigating the factors influencing customer satisfaction within the private banking sector, particularly concerning the relationship between the quality of digital banking services and customer perceptions. Aims: This study aims to analyze customer satisfaction with digital banking features provided by private sector banks, identifying key factors that contribute to satisfaction or dissatisfaction. Results: Utilizing a mixed-methods approach, quantitative data will be collected through structured surveys, complemented by qualitative insights from in-depth interviews. A minimum sample size of 50 participants will be targeted to ensure statistical power and generalizability of findings. Novelty: This research addresses a critical gap in understanding customer satisfaction within the context of digital banking, emphasizing the need for continuous innovation and improvement in service delivery. Implications: By identifying key determinants of customer satisfaction, the study offers actionable insights for banks to enhance digital services, build trust, and improve customer loyalty. The findings are expected to contribute to the broader discourse on digital banking, guiding strategic decision-making in a rapidly evolving financial landscape.